Implementation of the performance management system in the Gauteng Department of Agriculture and Rural Development - Lemao, Dineo (My University, 2016)
The performance management system was introduced in the South African public service with the intention to continuously manage performance by setting performance objectives, reviewing past performance, assessing current performance, improving poor performance, determining recognition and reward for good performance, and assisting with career planning. Research has revealed that although the performance management system has been implemented in government departments it has not achieved expected results. This study was undertaken as an attempt to investigate the factors leading to the challenges in implementing the performance management system in the Gauteng Department of Agriculture and Rural Development. To achieve this, semi-structured interviews were conducted with employees at different levels as well as a former trade union leader who was involved in the process of developing the Gauteng Provincial Government Policy on Performance Management and Development. Internal documents of the Department were also analysed. The themes identified led to a richer understanding of the factors affecting the implementation of the performance management system. The research findings indicate that although there is an understanding of performance management in the Department, implementation remains a challenge. The analysis of the responses indicated a great dissatisfaction with the current system. A few of the reasons are that not all managers show commitment towards the performance management system; some managers are not fair in the manner in which they conduct performance assessments and distribute rewards; it has failed to link performance outcomes to rewards in a meaningful manner; there is not much emphasis placed on personal and career development; and there are no measures put in place by supervisors to address employees who do not achieve the set performance targets. It is concluded that there is an urgent need for government to address the challenges experienced with the system, as at the moment, it is not meeting the objectives it was intended to meet.
A research report submitted to the faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Governance and Public Leadership) 2015
Keywords: Performance--Management; Employees--Rating of; Public administration--South Africa